2014
DOI: 10.1016/j.molcel.2014.02.024
|View full text |Cite
|
Sign up to set email alerts
|

An mRNA-Derived Noncoding RNA Targets and Regulates the Ribosome

Abstract: SummaryThe structural and functional repertoire of small non-protein-coding RNAs (ncRNAs) is central for establishing gene regulation networks in cells and organisms. Here, we show that an mRNA-derived 18-nucleotide-long ncRNA is capable of downregulating translation in Saccharomyces cerevisiae by targeting the ribosome. This 18-mer ncRNA binds to polysomes upon salt stress and is crucial for efficient growth under hyperosmotic conditions. Although the 18-mer RNA originates from the TRM10 locus, which encodes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
98
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(103 citation statements)
references
References 36 publications
5
98
0
Order By: Relevance
“…They can be powerful tools for the visualization of mRNAs being translated and synthesized proteins. Ribosome-binding proteins and sRNAs interacting with the ribosomes can also be studied [35,36]. Here, we have confirmed in vivo the presence of the trans-translation effector transfer-messenger RNA (tmRNA) [37] and the SprD regulator RNA [38] into the ribosomal fractions.…”
Section: Resultsmentioning
confidence: 56%
“…They can be powerful tools for the visualization of mRNAs being translated and synthesized proteins. Ribosome-binding proteins and sRNAs interacting with the ribosomes can also be studied [35,36]. Here, we have confirmed in vivo the presence of the trans-translation effector transfer-messenger RNA (tmRNA) [37] and the SprD regulator RNA [38] into the ribosomal fractions.…”
Section: Resultsmentioning
confidence: 56%
“…It has been shown that using LNAs instead of standard antisense DNA probes increases sensitivity in detecting short RNA at least 10-fold, with the same specificity to the target molecule (Válóczi et al 2004). LNA probes allowed, for instance, to detect small amounts (-27 000 molecules/cell) of 18-mer RNA, a regulatory ribosome-associated molecule needed for stress-adaptation in S. cerevisiae (Pircher et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Although sdRNAs were observed in very low abundance within our cDNA libraries, their regulatory potential cannot be excluded. Our recent studies demonstrated that even a relatively small amount of 18-mer rancRNA (-27 000 molecules/cell) is sufficient to substantially influence global ribosome activity (-200 000 ribosomes/cell) and switch translation in the cell (Pircher et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a group of novel small noncoding RNAsthat associate directly with the ribosome have been identified in yeast, although their biological function, if any, was unclear(Zywicki et al, 2012). In this issue of Molecular Cell ,Pircher et al (2014) show that the most abundant of these ncRNAs is derived from an mRNA, is constitutively bound to the ribosome itself,and modulates global translation levels in response to acute hypertonic stress (Pircher et al 2014). …”
mentioning
confidence: 99%
“…Pircher et al (2014) identifieda stable 18-nt ncRNAderived from the exon on the TRM10 mRNA that predominantly associates with ribosomes in all growth conditions. In favorable osmotic conditions the 18-mer ncRNA associates with nontranslating 60S ribosomal subunitsand 80S ribosomes,but only a very small portion associates with translating ribosomes, i.e.…”
mentioning
confidence: 99%